Sources of Extension Information for Growers in Miami-Dade County - Rafael Muñoz-Carpena; Jonathan H. Crane; Glenn Israel (EDIS)
This fact sheet reports on the part of a survey that addressed growers sources of notification and information on water management and conservation in Miami-Dade County. This document is ABE349, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2005.